Color Vision and the Railways. Issue 2 (February 2015) - Dain, Stephen J.; Casolin, Armand; Long, Jennifer
ABSTRACT Purpose There are two currently available lantern tests that have their design based solely on the practices of the rail industry. These are the CN Lantern (CNLAN) used on the Canadian Railways and the Railway LED Lantern Tests (RLLT). In the same way that the signaling practices differ in the two jurisdictions, the design of the lanterns also differ. The CIE (Commission Internationale de l'Éclairage)-recommended color vision standards for transport predate both lanterns. The study was undertaken to assess the appropriateness of these lanterns in CIE Color Vision Standard 1. CIE Standard 1 is called "Normal color vision" but some very mild anomalous trichromats may pass the specified "lantern test that presents a high level of difficulty." Methods The lantern tests were undertaken by 46 color vision–normal and 37 color vision–deficient subjects. Results Subjects made more errors on the RLLT, and the pattern of errors is different, partly because there are blank presentations in the RLLT and "no light" is an acceptable response. The two lanterns showed agreement on the pass/fail categorization of 73 of the 83 subjects. The RLLT fails more color vision–normal subjects. Conclusions Despite the different construction principles, the RLLT and CNLAN have pass/fail levels that are comparable with the Holmes-Wright Type B lantern, which is nominated in CIE Color Vision Standard 1 but is no longer commercially available. The higher failure rate of color vision–normal subjects on the RLLT has been addressed by changing the intensities of the two darkest red lights.